Wastewater bacterial communities bring together broad-host range plasmids, integrons and a wide diversity of uncharacterized gene cassettes - Moura, Alexandra (2020)
To investigate the mobile gene pool present in wastewater environments, total community DNA was obtained from two distinct raw effluents: urban and slaughterhouse wastewaters. Bacterial community structure was evaluated by DGGE analysis of 16S rRNA gene fragments. Detection of broad-host-range plasmid sequences and integrase encoding genes was carried out through PCR and Southern hybridization. Gene cassette libraries were obtained using primers targeting consensus sequences that flank gene cassettes. Analysis of DGGE profiles revealed a complex and distinct bacterial community among effluents (similarity<25%). Despite that, All plasmid-specific sequences searched (rep for IncN, trfA for IncP-1 and oriV for IncQ and IncW) and integrase genes were present in both effluents. Gene cassettes recovered from clone libraries showed low homology with genes encoding putative enzymes involved in the metabolism of amino sugars, cell wall synthesis, motility, gene regulation, intercellular signalling and secretion pathways and in the synthesis of cellulose, folic acid and antibiotics. Additionally, in the majority of clones, no identifiable open reading frames homologues were found in the databases. According to our results, wastewater environments promote the development of bacterial communities that support and bring together different types of molecular elements that, in association, play a major role in bacterial adaptation and evolution.